Relationship between the Use of Hormonal Contraception and Spotting Incidents in the Sonuo Village Health Center Area - Suriani G. Bolaang; Widia Shofa Ilmiah; Rizful Maulina (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
The use of hormonal contraception is a common method used by women of childbearing age to prevent pregnancy. However, this method is often associated with side effects, one of which is spotting or light bleeding outside the menstrual cycle. This study aims to analyze the relationship between the type of hormonal contraception and the incidence of spotting in the Sonuo Village Health Center  area. This study used a quantitative design with a cross-sectional approach. The sample consisted of 37 respondents selected by total sampling. Data were collected through questionnaires and analyzed using the chi-square test with the help of SPSS software. The results showed that the majority of respondents used injectable contraception (62.2%), followed by implants (24.3%) and pills (13.5%). Most injectable users experienced spotting (82.6%), while implant users more often experienced amenorrhea (77.8%). The chi-square test showed a significant relationship between the type of hormonal contraception and the incidence of spotting (p-value = 0.000). The conclusion of this study is that the type of hormonal contraception affects the incidence of spotting, where injectables cause spotting more often than other methods. Education about the side effects of hormonal contraception needs to be increased so that users can choose a method that suits their body condition.